PROCESSING EFFECT ON ANTI-NUTRITIONAL AND MICROBIOLOGICAL PROPERTIES OF TRIFOLIATE YAM FLOUR VARIETIES - Chukwuka, Eze Paul; Ugwuanyi-Nnadi, Obiageli (Journal on Processing and Energy in Agriculture, 2025)
This research investigated whether 72 hours of fermentation can eliminate or reduce those harmful microorganisms and chemicals in the food content of the trifoliate yam that impose several challenges in human life and exploit and improve the numerous benefits associated with trifoliate yam. Freshly harvested trifoliate yams were subjected to natural fermentation for 72 hours, dried, and milled to produce trifoliate yam flour. The anti-nutritional and microbiological properties of the processed flour were determined. Fermentation significantly reduced the anti-nutritional properties of the trifoliate yam flour at p < 0.05 apart from flavonoid which increased at 72 hours fermentation period. For microbiological properties mould count, yeast count, and S.aureus were only detected and their average values for the unfermented and fermented samples were 31.66 x 103, 18.66 x102, 25.00 x104 and 35.33 x 103, 27.33 x 102, 38.66 x 104 respectively. It is therefore concluded that the fermentation reduced anti-nutritional properties to an extent that is friendly to mankind, increased the basic required minerals necessary to combat malnutrition and inadequate supply of protein-based food, and has a higher level of general acceptability.